Highlights of Discoveries for δ Scuti Variable Stars From the Kepler Era - Guzik, Joyce Ann (Frontiers in Astronomy and Space Sciences, 2021)
The NASA Kepler mission (2009-2018) left a legacy of data and discoveries, finding thousands of exoplanets, and also obtaining high-precision long time-series data on hundreds of thousands of stars, including many types of pulsating variables. Here we highlight a few of the ongoing discoveries from Kepler data for delta Scuti pulsating variables, which are core hydrogen-burning stars of about twice the mass of the Sun. We discuss many unsolved problems surrounding the properties of the variability in these stars, and the progress enabled by Kepler data in using pulsations to infer their interior structure, a field of research known as asteroseismology.